Indians Richer but Less Happy Today, Here the Plausible Five Reasons Why? - K. Sagar (Indian Journal of Psychiatric Nursing)
India has been ranked 133rd among 156 countries in the United Nations' World Happiness Report 2018, 15 places down from its position in 2015. This is despite the report's finding that India's per capita gross domestic product (GDP), a measure of the standard of living, and healthy life expectancy, a marker of well-being, have trended upward over the last 3 years. At the same time, socioeconomic inequity is preventing per capita GDP growth from translating into happier people. This is not to say that higher income does not matter. However, once these needs are fulfilled, they stop experiencing greater happiness with rising income if there is also growing inequality, as it leads to unfavorable comparisons. In the last 3 years, Indians have reported experiencing fewer positive emotions and more negative emotions, two variables that influence the World Happiness Ranking. Did you experience happiness and enjoyment during a greater part of yesterday? Did you smile or laugh a lot yesterday? Participants' responses to these questions made up the positive emotion variable, called “positive affect.” To what extent did you experience worry, sadness, and anger yesterday? Participants' responses to this question made up the negative emotion variable, called the “negative affect.” Here, in this article, there are five plausible reasons how happiness eludes India. However, we have a long way to go. These happiness rankings remind the loopholes in our system. India needs to work faster to reduce inequality and to ensure freedom and well-being. Happiness ministry is the need of the hour in India.